Rewriting Westphalia and Reviving Bandung: The Historical Trajectory of Nahdlatul Ulama’s Global Islamic Vision - Sus Eko Ernada (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2025)
This paper explores how the Muslim world today faces a fragmentation that echoes Europe's bloody religious wars prior to the Treaty of Westphalia (1648) and the colonial subjugation that triggered the Bandung Conference (1955). At a time when sectarianism, radicalism, and external securitisation threaten the coherence of Islamic civilisation, Nahdlatul Ulama (NU), Indonesia's largest Muslim organisation, emerges as a unique actor striving for renewal. This article examines NU's global initiatives through the dual historical lenses of Westphalia and Bandung, proposing that NU seeks not only to establish a "Muslim Westphalia"—an order based on peaceful coexistence among Islamic traditions—but also to reignite the "Spirit of Bandung"—a decolonial movement for Islamic dignity, independence, and pluralism. Through initiatives like Humanitarian Islam and the R20 Forum, NU offers a model of civil Islam that challenges both internal extremism and external domination. Furthermore, the article situates NU's actions within the broader theoretical frameworks of international relations, highlighting the organisation's attempt to create an "Islamic international society" based on pluralism, sovereignty, and mutual respect, echoing the foundations  of  the  Westphalian  system  but  adapted  to  the  Muslim  world's  realities. At a time when global governance struggles to reconcile power with ethics, NU's experiment offers a vital blueprint for a future shaped by moral leadership rather than coercive dominance. Ultimately, NU's efforts represent a critical, if precarious, experiment in building a new Islamic global order rooted not in hegemony or militarism but in ethical leadership, pluralism, and the global public good, offering an alternative vision for the future of international Islamic engagement.